Korupsi dalam Perspektif Al-Qur’an: Studi terhadap Tafsir Al Manar Karya Muhammad Rasyid Ridha dan Tafsīr FῙ Zhilālil Qur’an Karya Sayyid Quthb - Muhammad Fajri; Ahmad Syukri; Ansusa Ansusa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of the head of the Madrasah's academic supervision in improving the performance of teachers at MTs Darurrahman Rimbo Bujang, Tebo Regency. The research method used is qualitative with a descriptive approach, where data is collected through in-depth interviews, observations, and document analysis. Interviews are conducted with the head of the Madrasah, teachers, and other educational staff to gain a comprehensive understanding of the academic planning and supervision processes implemented. Direct observations of teaching and learning activities, along with document analysis of the work plans, are carried out to delve into the implementation of planned programs. The findings indicate that the head of the Madrasah's academic planning is crucial for enhancing teacher performance. The head of the Madrasah develops a structured plan involving all relevant stakeholders, setting clear goals, and planning periodic training programs. The implementation of academic supervision is conducted through a collaborative approach, where the head of the Madrasah and the supervision team provide constructive feedback to teachers following direct classroom observations. The follow-up of the supervision is also a critical aspect, with a report on supervision results being prepared and regular meetings held to evaluate teachers' progress. With this follow-up, it is expected that teachers receive the necessary support for ongoing development, creating a culture of reflection and continuous improvement in the learning process.